22.9k views
4 votes
Simplify (7t^2+9)+(6t^2+8)


2 Answers

6 votes

Assignment:
\bold{Simplify \ Equation: \ \left(7t^2+9\right)+\left(6t^2+8\right)}

<><><><><><><>

Answer: ➣
\boxed{\bold{13t^2+17}}

<><><><><><><>

Explanation:
\downarrow\downarrow\downarrow

<><><><><><><>

➤ [ Step One ] Remove Parenthesis: (a) = a


\bold{7t^2+9+6t^2+8}

➤ [ Step Two ] Group Like Terms


\bold{7t^2+6t^2+9+8}

➤ [ Step Three ] Combine Similar Elements:
\bold{7t^2+6t^2=13t^2}


\bold{13t^2+9+8}

➤ [ Step Four ] Add Numbers:
\bold{9+8=17}


\bold{13t^2+17}


\bold{\rightarrow Mordancy \leftarrow}

User Maciej Treder
by
4.7k points
6 votes

Answer:

13t^2 +17

Explanation:

It helps to regroup the terms so like terms are together. Then you can more easily see how to combine them.

(7t^2 +9) + (6t^2 +8) = 7t^2 + 9 + 6t^2 + 8

= 7t^2 + 6t^2 + 9 + 8

= t^2·(7 + 6) + (9 +8)

= 13t^2 +17

User Apurva Thorat
by
4.5k points